Plebiscito - Kalil, Daniela (2013)
The preamble of the Constitution of the Federative Republic of Brazil of 1988, called Citizen Constitution states that representatives of the Brazilian people gathered in the National Constituent Assembly to institute a Democratic State. This democratic state founded on some fundamental principles constitutionally expressed, including, sovereignty and citizenship, which are prerequisites for citizens' political participation in public affairs. All these concepts are interrelated, complementing each other and constitute a set of principles, rights and duties, which provides the practical existence of democratic political order. The challenge of Brazilian society, as well as of other contemporary democratic societies, is to promote the improvement and accomplishment of popular participation in the State s life, which reveals a very complex task from the moment one understands that, first, it is imperative that become effective the rights and guarantees proclaimed in the Constitution. Aside from this need, it is essential, also, that people dispose of participatory mechanisms, which enjoy a truly legal and political framework that aims at the achievement, execution and result. In a country whose highest law prescribes that all power emanates from the people, who may exercise it in a direct form, popular participation is a prerequisite for the fulfillment of the purposes of a democratic State under law. The plebiscite comes as a fundamentally valuable tool for the achievement and consolidation of participatory democracy.